(Un)Coupled thrust belt‐foreland deformation in the northern Patagonian Andes: New insights from the Esquel‐Gastre sector (41°30′–43°S). Issue 11 (19th November 2016) - Savignano, E.; Mazzoli, S.; Arce, M.; Franchini, M.; Gautheron, C.; Paolini, M.; Zattin, M.
Abstract: The Patagonian Andes represents a unique natural laboratory to study surface deformation in relation to deep slab dynamics. In the sector comprised between latitudes 41°30′ and 43°S, new apatite (U‐Th)/He ages indicate a markedly different unroofing pattern between the "broken foreland" area (characterized by Late Cretaceous to Paleogene exhumation) and the adjacent Andean sector to the west, which is dominated by Miocene‐Pliocene exhumation. These unroofing stages can be confidently ascribed to inversion tectonics involving reverse fault‐related uplift and concomitant erosion. Late Cretaceous‐Paleogene shortening and exhumation are well known to have affected also the thrust belt sector of the study area during a prolonged stage of flat‐slab subduction. Therefore, the different ages of near‐surface unroofing documented in this study suggest coupling of the deformation between the thrust belt and its foreland during periods of flat‐slab subduction (e.g., during Late Cretaceous‐Paleogene times) and dominant uncoupling during periods of steep‐slab subduction and rollback, even when these are associated with high convergence rates (i.e., > 4 cm/yr), as those documented in Miocene times for the Patagonian Andes. Key Points: New apatite (U‐Th)/He ages were obtained for the Patagonian Andes at latitudes 41°30'‐43°S The "broken foreland" area was characterized by Late Cretaceous to Paleogene exhumation Thrust belt‐foreland (un)coupling of the deformation depends on steep‐ versus flat‐slab subduction